2002
DOI: 10.1538/expanim.51.465
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Correction Technique for QT Interval in Long-Term Telemetry ECG Recording in Beagle Dogs.

Abstract: The establishment of a new rate-correction method for the QT interval is presented for long-term telemetry ECG recording in free-moving beagle dogs. First, in order to define the QT-RR relation to derive the correction formula, the diurnal variations of the QT and RR intervals and the influencing factors were analyzed, and the QT-RR regression coefficient beta was estimated under various conditions: steady and non-steady states of animal, light and dark periods, and over 24 h. In the results, the diurnal rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…Based on linear regression analysis of QTc interval against RR interval, we found that individual rate correction in accordance with the analysis of covariance (Miyazaki and Tagawa, 2002) best corrected the effect of RR interval on QT interval in comparison with the generic formulas tested. When corrected using the individual correction method, the QT-prolonging drugs tested showed QTc interval prolongation, whereas the non-QT-prolonging drugs did not show QTc interval prolongation, suggesting that the marmoset telemetry model has potential to be utilized in prediction of a drug's liability to lengthen QTc interval in humans.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on linear regression analysis of QTc interval against RR interval, we found that individual rate correction in accordance with the analysis of covariance (Miyazaki and Tagawa, 2002) best corrected the effect of RR interval on QT interval in comparison with the generic formulas tested. When corrected using the individual correction method, the QT-prolonging drugs tested showed QTc interval prolongation, whereas the non-QT-prolonging drugs did not show QTc interval prolongation, suggesting that the marmoset telemetry model has potential to be utilized in prediction of a drug's liability to lengthen QTc interval in humans.…”
Section: Discussionmentioning
confidence: 84%
“…However, these standard correction formulas have been shown to have limitations in comparison with the new approach of finding the relationship in an individual (Miyazaki and Tagawa, 2002). As with telemetry studies in other species (Miyazaki and Tagawa, 2002;Kano et al, 2005;Holzgrefe et al, 2007), with common marmosets the individual method showed better corrections than both traditional formulas, although the corrections from Bazett's were nearly comparable. Nifedipine, which has no QT-prolonging risk in clinic, was reported to cause tachycardia and false QTc interval prolongation in a canine telemetry study using Fridericia's formula (Toyoshima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QT-RR relationship varies depending on each condition of measurement, for example, under the free-moving condition (7), under the restraint condition in a sling (13), and under the anesthetized condition (14). The QT-RR relation also varies depending on the method of data sampling and / or data analysis, for example, averaged QT-RR plots (15) versus beat-to-beat QT-RR plots (16) and QT-RR plots from a group of animals (9) versus QT-RR plots from individual animals (8). Therefore, the previously recommended QT-RR model would not necessarily provide the optimal fit for the telemetry data used in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bazett's and Fridericia's formulas as correc-tion methods are the most frequently used in dogs as well as humans (4 -6), they have been questioned due to the over-correction at faster heart rates and undercorrection at slower heart rates (7 -9). Lately, although the rate-correction optimized for each subject has been recommended for dogs as well as humans (8,10), how much the individual subject correction can improve the sensitivity and specificity compared to the generic QTc formulas has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%